Jumping the Gap: developing an innovative product from a Social Network Analysis perspective - Martín Ferron, Leandro (AWARI, 2022)
The creation of new products from the bonding between science and industry incorporates aspects that can be reviewed based on the nature of the academy-business bonds, the structure of the science & technology systems, or the models of academy-industry articulation. This research proposes a novel approach based on the analysis of a case study and uses the perspective of social network analysis to reconstruct the academic-state-business links necessary for the generation of innovation. The main source of data was the narration of a key informant, taking the innovative product as the ego of the network. Knowledge circulation pathways were identified, as well as subgroups of nodes whose attributes are associated with the product's transfer, development, and financing actions. The actor with the highest degree of centrality in the network belongs to the academic sector, and he operated as a bridge that bonded the academic and state sectors. This could be an indication that the promotion of this type of profile within the academic sector could boost the development of innovative products based on scientific knowledge.